Peran Komunikasi Pemerintah Kota Padangdalam Penanganan Tawuran Di Kota Padang - Charlie Doma Putra; Emeraldy Chatra; Ernita Arif (CV. ITTC INDONESIA, 2025)
This study examines the role of government communication in handling youth gang fights in Padang City, which has become a complex social problem due to a significant increase in cases (40 cases in 2022), the involvement of youth gangs, the escalation of armed violence, and the impact on the city's image as a center of education and tourism. Objective of this study is to explore the dynamics of communication among stakeholders in addressing youth gang violence in Padang City. The qualitative research method uses a phenomenological approach applied through in-depth interviews with 11 key informants (government officials, police, teachers, community leaders, parents, and gang members), observations, and analysis of policy documents and police data. The research findings reveal that: (1) The dynamics of communication among stakeholders are reactive, fragmented, and lack intensity, with coordination only becoming optimal post-incident; (2) The perspectives of youth indicate that involvement in fights is driven by environmental influences, peer pressure, curiosity, and identity-seeking, as well as a lack of understanding of risks; (3) Communication narratives focus on law enforcement (patrols, school sanctions) and preventive programs based on local wisdom (Barisan Dubalang), but are not yet integrated with psychosocial approaches; (4) Barriers to effectiveness include sectoral egoism, temporary communication (only during incidents), and weak synergy of sustainable programs. This study concludes that there is a need to transform the communication model to be collaborative, preventive, and based on the needs of adolescents, by utilizing digital technology and strengthening the role of families and traditional leaders as strategic partners.